Repeated exposure to transient obstructive sleep apnea-related conditions causes an atrial fibrillation substrate in a chronic rat model - Linz, Benedikt; Hohl, Mathias; Lang, Lisa; Wong, Dickson W. L.; Nickel, Alexander G.; Torre, Carolina de la; Sticht, Carsten; Wirth, Klaus; Boor, Peter; Maack, Christoph; Speer, Thimoteus; Jespersen, Thomas; et al. (Heart rhythm, 2021)
Background - High night-to-night variability in obstructive sleep apnea (OSA) is associated with atrial fibrillation (AF). Obstructive apneas are characterized by intermittent deoxygenation-reoxygenation and intrathoracic pressure swings during ineffective inspiration against occluded upper airways. - Objective - We elucidated the effect of repeated exposure to transient OSA conditions simulated by intermittent negative upper airway pressure (INAP) on the development of an AF substrate. - Methods - INAP (48 events/4 h; apnea-hypopnea index 12 events/h) was applied in sedated spontaneously breathing rats (2% isoflurane) to simulate mild-to-moderate OSA. Rats without INAP served as a control group (CTR). In an acute test series (ATS), rats were either killed immediately (n = 9 per group) or after 24 hours of recovery (ATS-REC: n = 5 per group). To simulate high night-to-night variability in OSA, INAP applications (n = 10; 24 events/4 h; apnea-hypopnea index 6/h) were repeated every second day for 3 weeks in a chronic test series (CTS). - Results - INAP increased atrial oxidative stress acutely, represented in decreases of reduced to oxidized glutathione ratio (ATS: INAP: 0.33 ± 0.05 vs CTR: 1 ± 0.26; P = .016), which was reversible after 24 hours (ATS-REC: INAP vs CTR; P = .274). Although atrial oxidative stress did not accumulate in the CTS, atrial histological analysis revealed increased cardiomyocyte diameters, reduced connexin 43 expression, and increased interstitial fibrosis formation (CTS: INAP 7.0% ± 0.5% vs CTR 5.1% ± 0.3%; P = .013), which were associated with longer inducible AF episodes (CTS: INAP: 11.65 ± 4.43 seconds vs CTR: 0.7 ± 0.33 seconds; P = .033). - Conclusion - Acute simulation of OSA was associated with reversible atrial oxidative stress. Cumulative exposure to these transient OSA-related conditions resulted in AF substrates and was associated with increased AF susceptibility. Mild-to-moderate OSA with high night-to-night variability may deserve intensive management to prevent atrial substrate development.
Gesehen am 12.08.2021